Inactivation of enterotoxic and non-enterotoxic Staphylococcus aureus strains by high pressure treatments and evaluation of its impact on virulence factors - Baptista, Inês
Staphylococcus aureus is responsible for a large spectrum of diseases, including staphylococcal food poisoning (SFP), due to its ability to produce enterotoxins. To prevent the development of SFP, effective food preservation methods are needed. High pressure processing (HPP) uses pressures, between 100 and 600 MPa, to inactivate pathogenic and spoilage microorganisms. In this study, HPP treatments (450 MPa and 600 MPa, both for 15 and 30 min, at 20 C) were applied in three different strains of S. aureus in the stationary growth phase and reduction effectiveness was assessed. A non-enterotoxic strain ATCC 6538 and two enterotoxic strains 2153 MA (with enterotoxin A) and 2065 MA (with enterotoxin A, G, I) were used. It was verified that the non-enterotoxic strain was the most resistant to HPP, not being completely inactivated within 30 min at 600 MPa. Additionally, it was demonstrated that HPP had no effect on virulence factors (enterotoxins, b-hemolysin, lipase, lecithinase, coagulase, thermonuclease, catalase), and also in mannitol fermentation capacity and methicillin susceptibility. HPP treatments also proved to be less effective in the strain with higher carotenoids content (non-enterotoxic strain). The results of this study show that S. aureus HPP barotolerance might be related not only to the presence of enterotoxins but also to carotenoids level, although these two factors may not be the only mechanisms responsible for the distinct sensitivity/resistance to HPP shown by different strains of S. aureus.